The effects of the foot types and structures of the inner arch support bands on ground reaction force variables and sensations during 2nd vertical ballet jump - Kim, J.; Yi, K. (Korean Journal of Sport Biomechanics, 2017)
Objective: The purpose of this research was to establish the differences of ground reaction force variables and sensations according to the foot types and the structures of the inner arch support band during 2nd vertical ballet jump. Method: 12 Female ballet majors in their twenties who have danced for more than 10 years and had no injuries were selected for this research. Independent variables consist of the foot type (pes rectus, pes planus) and the structure of the inner arch support band (no band, x-shaped, linear shaped). Dependent variables consist of ground reaction force variables and relative wearing sensation. Results: The impact decreased the most when x-shaped bands were used on pes rectus and rigid pes planus. When linear-shaped bands were used on flexible pes planus, the impact decreased. Conclusion: The bands also helped reduce the impact on pes rectus. Furthermore, it is clear that according to the foot type, the impact reducing band structures perform differently. The inner arch support bands were necessary for jump training for any foot type.